Analisis Daerah Rawan Kecelakaan Lalu Lintas pada Jalan Tjilik Riwut Kota Kasongan Kabupaten Katingan Provisi Kalimantan Tengah - Rusnana Suletae; Desriantomy; Ina Elvina (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Katingan Regency is one of the areas known to be prone to traffic accidents in Central Kalimantan Province. As a result of these accidents, there are many casualties. Therefore, it is necessary to conduct research to determine the level of accidents that occur on the Tjilik Riwut Kasongan road section. The purpose of this study is to analyze accident data on the Tjilik Riwut Kasongan road, analyze the location of traffic accident hotspots on the road, analyze the main factors causing accidents and provide recommendations to relevant agencies to reduce the accident rate on the road. The results of the accident analysis on the Tjilik Riwut Kasongan road carried out for 5 years (2018-2022) accidents amounted to 51 events. Based on the Accident Equivalent Number (AEK) method and the Upper Control Limit (UCL) method, it shows that segment 1(Km 0+000 -Km 5+000) is a traffic accident-prone area. The main cause of accidents is due to human factors and the influence of road conditions. The alternative countermeasures are patching potholes, cleaning drainage, leveling asphalt patching, adding road medians, repainting faded signs, installing traffic signs and socializing traffic safety and legal discipline in traffic.